Spy Walker: A Convenient Way to Assess Gait in Walker Assistive Devices - Viegas, Vítor (2018)
Trabalho apresentado em 2018 IEEE International Instrumentation and Measurement Technology Conference, 14-17 maio 2018, Houston, TX, USA